Clinical and Epidemiological Features of Allergies in Schoolchildren of the Chechen Republic: Results of an Epidemiological Study - Aset Kh. Ibisheva; Saihat A. Shamsadova; Leyla S. Namazova-Baranova (Union of pediatricians of Russia, 2023)
Background. One of the topical issues of modern medicine is the widespread increase in the incidence of allergic pathology. Objective. The aim of the study is to investigate clinical and epidemiological features of allergies in schoolchildren of the Chechen Republic. Methods. We performed clinical and diagnostic verification of allergies according to clinical guidelines in patients who positively answered the ISAAC questionnaire (n = 80) - 46 first-grade and 34 eighth-grade pupils. The first diagnostic step on studying the clinical manifestations in observed children was the history taking, complaints, physical examination. Laboratory and instrumental diagnosis included: IgE total, detection of skin sensitivity to allergens via standard pollen, domestic, epidermal, and food allergens (produced by I.M. Mechnikov Research Institute of Vaccines and Sera, Stavropol Research Institute of Vaccines and Sera), revealing of allergen-specific antibodies, component-divided allergen diagnosis via indirect immunofluorescence with ImmunoCAP analyzer, respiratory function evaluation with CareFusion, nitric oxide level detection in exhaled air via portable NObreath analyzer. If needed, specialised medical consultation were performed. Results. Asthma was detected in 37 (46.3%) children, allergic rhinitis (AR) - in 37 (46.3%), atopic dermatitis (AD) - in 5 (6.3%) according to the results of our study. The most common combination of medical conditions in examined patients was combination of asthma and AR. There were no statistically significant differences in age groups. No gender differences were reported in the study. The highest incidence of asthma and AR was revealed in city residents (p < 0.05), while the AD incidence in the city and rural areas did not differ significantly. The sensibilization spectrum analysis in schoolchildren of the Chechen Republic revealed predominance of sensitivity to pollen (ragweed, herd grass) and domestic allergens (Dermatophagoides pteronyssinus, Dermatophagoides farinae). Sensitization to food allergens in children of the Chechen Republic did not have significant differences in the frequency of occurrence of individual allergens, that is, unlike pollen and household sensitization, a regional rating on the dominance of certain food allergens was not obtained. Sensibilization to epidermal allergens was also less common, the predominant one was the cat allergen. Conclusion. Thus, the first study on the territory of the Chechen Republic carried out according to the ISAAC program has revealed high prevalence of allergies in schoolchildren. Moreover, regional features of sensibilization structure have been identified. It will allow us to maintain economically optimal diagnosis of allergic diseases in children living in the Chechen Republic.